UPAYA GURU DALAM MENGINGKATKAN MINAT BELAJAR SISWA DENGAN MENGGUNAKAN METODE DISKUSI DARING DI SMP IX KOTA TEBING TINGGI - Ridwan Syahdana Nasution (Fakultas Agama Islam, 2021)
This research is motivated by a phenomenon that the teacher's efforts to increase student interest in learning through online classroom teacher guidance greatly affect the importance of learning interest through classroom teacher guidance for a student when online learning is carried out. In this case, the teacher's efforts are needed to increase students' interest in learning while online so that educational goals can be achieved perfectly. In this study using qualitative research methods. The data analysis technique used is data collection, data reduction, and conclusion drawing. This study shows that (1) there are 2 teacher strategies, the first is online, the second is offline (2) students are enthusiastic at the beginning of online learning, limited human resources, parents provide assistance at home, watch television, youtabe, cellphone (3) students' understanding level is difficult. better face to face, procrastinating time for students with high interest feel disadvantaged, for students with low interest feel happy.